2018
DOI: 10.1177/1071100718766655
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Vancomycin Treatment on Human Mesenchymal Stromal Cells During Osteogenic Differentiation

Abstract: Surgeons should exercise caution and consider the limited soft tissue envelope when applying vancomycin locally during foot and ankle surgery, especially during arthrodesis procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 17 publications
3
12
0
Order By: Relevance
“…Generally, more new bone formation was observed in the groups with a lower vancomycin concentration (1, 2, 4 g) compared with groups with higher vancomycin (6, 8, 10 g), which revealed that the process of bone formation was restricted by high-dose vancomycin. These results were in agreement with previous in vitro studies, whereby high-dose vancomycin could impair the viability and osteogenic differentiation of mesenchymal stem cells 32 , 33 .…”
Section: Discussionsupporting
confidence: 93%
“…Generally, more new bone formation was observed in the groups with a lower vancomycin concentration (1, 2, 4 g) compared with groups with higher vancomycin (6, 8, 10 g), which revealed that the process of bone formation was restricted by high-dose vancomycin. These results were in agreement with previous in vitro studies, whereby high-dose vancomycin could impair the viability and osteogenic differentiation of mesenchymal stem cells 32 , 33 .…”
Section: Discussionsupporting
confidence: 93%
“…There have been several reports on the effects of vancomycin on osteogenic differentiation. The general view is that vancomycin does not adversely affect the osteogenic differentiation of human osteoblasts and human bone marrow-derived MSCs at effective antimicrobial concentrations and higher concentrations[14,24,25]. However, it has also been reported that vancomycin inhibits the osteogenic differentiation of bone marrow-derived MSCs at a concentration of 200 μg/mL[16].…”
Section: Effects Of Various Antimicrobial Agents On Osteogenic Differmentioning
confidence: 99%
“…Previous in vitro studies on cellular toxicity of vancomycin have been conducted on relevant cell types within a joint. 1,3,9,19 Bariteau et al 3 found that exposing human mesenchymal stromal cells (hMSCs) to 5000 µg/mL vancomycin for 3 days resulted in significantly decreased cell viability, proliferation, and mineralization. Chu et al 9 established a dose-dependent increase in cell death for hMSCs exposed to vancomycin for 24 hours, starting at 400 µg/mL.…”
Section: Discussionmentioning
confidence: 99%